The Bloomsbury handbook of popular music and youth culture - 1963- Bennett, Andy. (New York Bloomsbury Academic, 2023)
offers a critical overview of key themes and debates in the field of popular music and youth culture studies"--
Part 1: Theory. The Past, Present and Future of Subculture / Ross Haenfler ; 'The Postsubculturalist' : Some Critical Reflections Over Twenty Years On / David Muggleton ; Music Scenes / Geoff Stahl ; The Milieu Culture of Punk : Beyond the Scene - A Guide to Thinking and Researching Culture / Pete Webb -- Part 2: Method. Ethnography, Popular Music and Youth Culture : An Anthropologist's Account / Evangelos Chrysagis ; Youth, Music and Social Network Analysis / Nick Crossley ; Contributions for a Quantitative Approach to Contemporary Youth Cultures and Popular Music : A Case Study from South Europe / Paula Guerra ; 'Images and Words' : Textual Analysis and Its Uses for Metal Music Studies / Catherine Hoad ; Should We Call It Cine-cultural Studies? Cineworlding Popular Music and Youth Studies / Michael B. MacDonald -- Part 3: History. Counterculture and Youth Culture : Definitions, Drifts, Events, Music, Echoes / Sarah Hill ; Glam Rock : Youth Culture, Performativity and Sexuality / Jon Stratton ; Time to DIY : A History of Punk and Indie / Matthew Bannister ; The Dynamics of Dance : An Early History of Electronic Dance Music / Alex van Venrooij and Rens Wilderom ; Under a Groove : Rap, Hip-Hop and Their Glocalization / Stefano Barone -- Part 4: Identity. Structure and Historicity of Youth Music Tastes : A Brief Overview of Forty Years of Theoretical Debates / Hervé Glevarec and Raphaël Nowak ; 'Hey Girl, Don't Bother Me' : Gender, Sexuality and (In)visible Communities in Popular Music and Youth Culture / Sarah Raine and Eveleigh Buck-Matthews ; Beyond Youth : Music Scenes and Ageing / Paul Hodkinson ; When We Were Young : Popular Music, Youth and Memory / Ben Green -- Part 5: Media. Youth Radio, Music Cities and the Role of Urban Sociability : Case Study of Radio KUT FM (Austin) and Triple R FM (Melbourne) / Andrea Baker ; Youth, Zines and Music Scenes / Ashleigh Watson ; Youth, Identity and Everyday Sound Environments in the Age of Digital Technologies / Raphaël Nowak ; Popular Music in a Brand Culture / Nick Carah and Kiah Hawker ; Singing and Soundtracking Identity : Youth, Music and Film / Scott Henderson -- Part 6: Place. Youth, Music and the City : A Mapping of Leeds in Five Scenes / Brett Lashua and Gabby Skeldon ; Rural (Un)cool : Alternative Geographies of Young People and Music / Lisa Nikulinsky ; Music Festivals and Youth / Chris Anderton ; Music, Youth and Virtual Spaces / Sian Lincoln ; Independent Music and Independent Music Scenes : From DIY-led Collectives to Individualized Professionals? / Robin Kuchar -- Part 7: Music-making. Youth and DIY Music and Media-making / Rosa Reitsamer ; Cultivating Community on YouTube and Expanding Through Social Media / Christopher Cayari ; Home Recording, Production and Young Musicians Working in the Context of the 'New' Music Industry / Richard Frenneaux ; Youth Culture, Technology and Tribute Entertainment / Georgina Gregory.
includes bibliographical references and index.
description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: bculture; music and youth; anthropology; popular music -- Social aspects; Youth -- Social life and customs